Greatest hits [compact disc] - Berkner, Laurie (Kidz Bop, 2025)
March like a dinosaur, swim like a fish, and walk like a penguin because your all-time favorite Laurie Berkner songs will finally be in one place! With songs like We are the dinosaurs, The goldfish, Waiting for the elevator, and so much more!